So the Problem is with the picture which is attached. Attempted Solution: for m2: F = m2a = T - m2g T = m2g then for m1: F = m1a = T a = T/m1 Then plug in: a = m2g/m1 then for all three blocks: F = (M = m1 = m2)a so: F= (M +m1 +m2) (M2g/m1) Now I'm pretty sure thats the right answer, but i need to know if my work is done correctly, every single part because I have to do this problem in front of the class . Moreover, how could I extend this problem. Like what would be a very related problem but make it a little more complicated and if you could provide a solution for the extension that would be awsome. Thanks for all responses in advance.